Endotine Midface for Soft Tissue Suspension in Zygoma Fracture. Issue 6 (September 2015) - Shim, Hyung-Sup; Seo, Bommie F.; Rha, Eun-Young; Byeon, Jun Hee
<x xml:space="preserve">Abstract</x> Abstract Treatment of zygomatic fractures necessitates dissection beneath the soft tissues of the cheek. Inadequate resuspension may lead to deformities, including cheek ptosis, lower lid ectropion, and lateral canthal dystopia. The authors present their experience using a biodegradable suspension device for cheek flap resuspension. Patients who received open reduction for unilateral zygomatic fracture between January, 2006 and December, 2013 at a single center were included in the study. Patients could choose whether or not to have Endotine midface inserted. Patients rated satisfaction on facial symmetry. Computed tomography (CT) at 15 months was assessed for soft tissue thickness at the level of the midpoint of the nasolabial fold on each side. Photographs at 15 months were viewed by 3 blinded plastic surgeons and rated for cheek drooping. The results for all 3 parameters were compared between the Endotine group and the control group. A total of 83 patients were included (43 in the Endotine group and 39 in the control group). Patient satisfaction scores were statistically higher (P = 0.03) in the Endotine group (3.70 ± 0.76) than the control group (2.85 ± 0.96). Computed tomography soft tissue thickness score ratio between affected and unaffected side was significantly lower (P < 0.001) in the Endotine group than the ratio in the control group. Photography evaluation score difference between affected and unaffected side for the Endotine group (0.70 ± 0.77) was significantly (P = 0.041) smaller than the control group (1.92 ± 1.24). Endotine midface is easy to apply and effective in repositioning the elevated cheek flap in zygomatic fracture patients.